Perancangan Sistem Informasi Jasa Bantu Pindah Berbasis Web - Erlin Elisa; Nurul Azwanti; Pastima Simanjuntak (LPPM Universitas Putera Batam, 2020)
This research is related to the design of a web-based application for moving assistance services, where this application aims to help people to find moving services such as transporting goods, arranging neatly in new places and other features, researchers get an idea of the problems that have been surveyed during The research process in the community is that it is difficult for people to find moving services in helping them to move houses, offices and even transport used building goods, this problem is what makes researchers interested in creating a web-based application specifically to solve this problem, the application design will use UML ( Unified Modeling Language) to describe the program design with the method used is the SDLC (system development life cycle) waterfall.